Impact of a large-scale market integration on the orientation of photovoltaic modules - Bogenrieder, Josef; Hosch, Patrick; Sölch, Christian; Brabec, Christoph (2016 13th International Conference on the European Energy Market (EEM), 2016)
To increase the amount of renewable energies, the Renewable Energies Act (REA) in Germany guarantees a fixed feed-in tariff for 20 years for every kilowatt-hour that is produced. Thus, photovoltaic modules were faced in the direction of the highest energy production. In this paper we investigate, if in a future energy system with a high share of renewable energy power and especially PV power, there is an incentive to face modules divergent because of an overproduction during noon. Hence, we modelled the PV generation for the states in Germany in detail as well as the spot market for the years 2014 and 2035 according to the Grid Development Plan of the German Transmission System Operators (TSO
Keywords: Engineering controlled terms: Electric power transmission; Photovoltaic cells; Power markets Development plans; Energy productions; Future energies; Market integration; Photovoltaic modules; Renewable energies; Renewable energy power; Transmission system operators Engineering controlled terms: Electric power transmission; Photovoltaic cells; Power markets Development plans; Energy productions; Future energies; Market integration; Photovoltaic modules; Renewable energies; Renewable energy power; Transmission system operators Engineering main heading: Commerce

Profitability and LCOE of Small Solar Battery Systemsthe German Case. (Smart Grid Solar - A Bavarian Smart Energy Project) - Stegner, Christoph; Luchscheider, Philipp; Bogenrieder, Josef; German, Reinhard; Brabec, Christoph (Proceedings of the 31st European Photovoltaic Solar Energy Conference (EU PVSEC 2015), 2015)
UnivIS-Import:2016-06-01:Pub.2015.tech.IMMD.IMMD7.profit

Wirtschaftlichkeitsbetrachtung von Haushaltsspeichern und realdatengestützte Untersuchung des elektrischen Eigenverbrauchs von PV-Strom - Stegner, Christoph; Bogenrieder, Josef; Auer, Sebastian; Luchscheider, Philipp; German, Reinhard; Brabec, Christoph (Nachhaltige Energieversorgung und Integration von Speichern: Tagungsband zur NEIS 2015, 2015)
UnivIS-Import:2016-06-01:Pub.2015.tech.IMMD.IMMD7.wirtsc